Pengabaian Pembelaan Unsur Kesengajaan terhadap Tindak Pidana Pendudukan Kawasan Hutan secara Tidak Sah dalam Sengketa Lahan Masyarakat dengan Perusahaan Pertambangan Batubara - Aji Devy Faziya (Jurnal Hukum Lex Generalis, 2025)
This research aims to analyze the convictions related to land management in forest areas carried out against community farmers in Gurimbang Village. This research was carried out by analyzing important aspects related to the basis of the conviction of community peasant groups in Kampung Gurimbang, forest area utilization companies, and coal mining activities by PT Berau Coal in Kampung Gurimbang, sorting out the delict of the letters that were the reason for the community's conviction, and conducting direct interviews with the convicts. The research results show that as long as the community lives in the area, the strengthening of the forest area has not been carried out until the determination process and the structure of the village management does not know exactly about the coordinate point of the forest area that has been determined. On the other hand, there is a license burden for coal mining companies in the area so that the community is in direct conflict with the company.